Analisis Perbandingan Kualitas Organoleptik Bolu Pandan Menggunakan Gula Pasir dan Gula Halus - Atikah, Rahadatul Aysi; Siregar, Juliana; Gusnita, Wiwik; Anggraini, Ezi (Al-DYAS, 2025)
This study is motivated by differences in the texture of sugar used in cake processing, particularly pandan sponge cake, where granulated sugar commonly used has a coarse texture and its impact on product quality has not been widely studied. The objective of the study is to analyze the effect of using granulated sugar versus powdered sugar on the quality of pandan sponge cake, covering aspects such as shape, volume, color, aroma, texture, and taste. This research is a true experimental study with three replications for each treatment. Data were collected through organoleptic tests using sensory evaluation methods by panelists to assess the cake quality based on predetermined indicators. Data analysis was conducted using the Independent Sample t-Test to determine significant differences between the two types of sugar. The results show that the use of powdered sugar significantly improves the volume, color, texture, and taste of pandan sponge cake compared to granulated sugar. These findings indicate that the choice of sugar type plays a crucial role in producing pandan sponge cake with superior sensory quality.